Communication of protection and rescue system in emergency situations caused by natural disasters - Ninković, Vladimir; Kešetović, Želimir (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
Even though communication is among the most important aspects of emergency management, crisis communication has been mainly viewed through the lenses of corporate sector, whilst public sector communication receives much less attention. The concept of crisis communication during emergency situations, in particular those caused by natural disasters, for some authors is not synonymous with the concepts of emergency communication and disaster communication. The main actors in the emergency situations belong to the public sector, be it at the national, regional or local level. During emergencies many communication problems may arise, in particular non-compliance with orders and the spread of rumours. In the Republic of Serbia, the Sector for Emergency Management of the Ministry of Interior is in charge of emergency management and communication in natural disasters. The role of the Sector was particularly salient during the disastrous floods in May 2014, when a state of emergency was declared on the territories of forty local self-government units (nine cities and thirty one municipality). In charge of communication with the local population, apart from the Sector HQ in Belgrade, were local emergency management headquarters, who had to combat the issues of non-compliance and rumours.